1999
DOI: 10.1086/307220
|View full text |Cite
|
Sign up to set email alerts
|

The Bispectrum as a Signature of Gravitational Instability in Redshift Space

Abstract: The bispectrum provides a characteristic signature of gravitational instability that can be used to probe the Gaussianity of the initial conditions and the bias of the galaxy distribution. We study how this signature is affected by redshift distortions using perturbation theory and highresolution numerical simulations. We obtain perturbative results for the multipole expansion of the redshift-space bispectrum which provide a natural way to break the degeneracy between bias and Ω present in measurements of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
437
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 286 publications
(453 citation statements)
references
References 35 publications
16
437
0
Order By: Relevance
“…At large scales, k \ 0.2 h Mpc~1, 2LPT reproduces the suppression of power compared to linear PT ; at smaller scales, the suppression is overestimated, as we approach the cuto † scale of the power spectrum and shell crossing also starts to play a role. The bottom panel of Figure 2 shows a similar comparison for the equilateral bispectrum ; the dotted line now corresponds to the redshift-space prediction at large scales from tree-level PT (Scoccimarro et al 1999a). We see that although tree-level PT breaks down at about k B 0.2 h Mpc~1, 2LPT continues to hold at smaller The dotted line shows the prediction of k 1 k 2 .…”
Section: Galaxy Biasing : Effects Of Stochasticitymentioning
confidence: 56%
See 1 more Smart Citation
“…At large scales, k \ 0.2 h Mpc~1, 2LPT reproduces the suppression of power compared to linear PT ; at smaller scales, the suppression is overestimated, as we approach the cuto † scale of the power spectrum and shell crossing also starts to play a role. The bottom panel of Figure 2 shows a similar comparison for the equilateral bispectrum ; the dotted line now corresponds to the redshift-space prediction at large scales from tree-level PT (Scoccimarro et al 1999a). We see that although tree-level PT breaks down at about k B 0.2 h Mpc~1, 2LPT continues to hold at smaller The dotted line shows the prediction of k 1 k 2 .…”
Section: Galaxy Biasing : Effects Of Stochasticitymentioning
confidence: 56%
“…tree-level PT . As noted before (Scoccimarro et al 1999a), the predictions of tree-level PT in redshift space break down at relatively large scales, due to the nonperturbative nature of the redshift-space mapping. Fortunately, since 2LPT performs the mapping exactly, the agreement with the numerical simulations is very good down to scales of k B 0.4 h Mpc~1.…”
Section: Galaxy Biasing : Effects Of Stochasticitymentioning
confidence: 77%
“…Detailed discussions of the projection effects are beyond the scope of this paper. We refer interested readers to a systematic study of the relativistic projection effects on the galaxy power spectrum [47] and on the squeezed galaxy bispectrum [10,22,48].…”
Section: Squeezed Matter Bispectrum As Measured By a Local Observermentioning
confidence: 99%
“…Assuming the line of sight component is along the z-axis, the fully non-linear relation between the real and redshift space power spectrum can be written as (Scoccimarro et al, 1999) first suggested by Peebles (1980) and modified by Fisher (1995) to take into account the density-velocity coupling. At small scales (as k increases) the exponential component damps the power, representing the impact of randomised velocities inside gravitationally bound structures.…”
Section: Modelling Non-linear Distortions To the Power Spectrum In Rementioning
confidence: 99%
“…The velocity divergence depends on Ω m and Ω Λ , in a standard ΛCDM cosmology, only through the linear growth rate, f (Scoccimarro et al, 1999).…”
Section: Dependence On Cosmological Modelmentioning
confidence: 99%